Role of microglia in regulating cholesterol and tau pathology in alzheimer's disease - Nanjundaiah, Shwetha; Chidambaram, Hariharakrishnan; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Cholesterol, a principal constituent of the cell membrane, plays a crucial role in the brain by regulating the synaptic transmission, neuronal signaling, as well as neurodegenerative diseases. Defects in the cholesterol trafficking are associated with enhanced generation of hyperphosphorylated Tau and Amyloid-beta protein. Tau, a major microtubule-associated protein in the brain, is the key regulator of the mature neuron. Abnormally hyperphosphorylated Tau hampers the major functions related to microtubule assembly by promoting neurofibrillary tangles of paired helical filaments, twisted ribbons, and straight filaments. The observed pathological changes due to impaired cholesterol and Tau protein accumulation cause Alzheimer's disease. Thus, in order to regulate the pathogenesis of Alzheimer's disease, regulation of cholesterol metabolism, as well as Tau phosphorylation, is essential. The current review provides an overview of (1) cholesterol synthesis in the brain, neurons, astrocytes, and microglia; (2) the mechanism involved in modulating cholesterol concentration between the astrocytes and brain; (3) major mechanisms involved in the hyperphosphorylation of Tau and amyloid-beta protein; and (4) microglial involvement in its regulation. Thus, the answering key questions will provide an in-depth information on microglia involvement in managing the pathogenesis of cholesterol-modulated hyperphosphorylated Tau protein.
Keywords: Alzheimer's disease; Amyloid-beta protein; Cholesterol; microglia; Tau hyperphosphorylation